Sononeoperfusion effect by ultrasound and microbubble promotes nitric oxide release to alleviate hypoxia in a mouse MC38 tumor model - Yi Zhang; Jing Zhang; Tingting Luo; Zhiping Cai; Guoliang Yang; Hui Li; Junshuai Wei; Qiong Zhu; Peijing Li; Xiaoxiao Dong; Zheng Liu (Ultrasonics Sonochemistry, 2023)
Tumor hypoperfusion not only impedes therapeutic drug delivery and accumulation, but also leads to a hypoxic and acidic tumor microenvironment, resulting in tumor proliferation, invasion, and therapeutic resistance. Sononeoperfusion effect refers to tumor perfusion enhancement using ultrasound and microbubbles. This study aimed to further investigate hypoxia alleviation by sononeoperfusion effect and explore the characteristics and mechanism of sononeoperfusion effect. To stimulate the sononeoperfusion effect, mice bearing MC38 colon cancers were included in this study and diagnostic ultrasound for therapy was set at a mechanical index (MI) of 0.1, 0.3, and 0.5, frequency of 3 MHz, pulse length of 5 cycles, and pulse repetition frequency of 2000 Hz. The results demonstrated that a single ultrasound and microbubble (USMB) treatment resulted in tumor perfusion enhancement at MI = 0.3, and nitric oxide (NO) concentration increased at MI = 0.3/0.5 (P < 0.05). However, there were no significant difference in the hypoxia-inducible factor-1α (HIF-1α) or D-lactate (D-LA) (P > 0.05) levels. Multiple sononeoperfusion effects were observed at MI = 0.3/0.5 (P < 0.05). For each treatment, USMB slightly but steadily improved the tumor tissue oxygen partial pressure (pO2) during and post treatment. It alleviated tumor hypoxia by decreasing HIF-1α, D-LA level and the hypoxic immunofluorescence intensity at MI = 0.3/0.5 (P < 0.05). The sononeoperfusion effect was not stimulated after eNOS inhibition. In conclusion, USMB with appropriate MI could lead to a sononeoperfusion effect via NO release, resulting in hypoxia amelioration. The tumors were not resistant to multiple sononeoperfusion effects. Repeated sononeoperfusion is a promising approach for relieving tumor hypoxia and resistance to therapy.